Reserve Prices as Signals - Onur A. Koska; Frank Stähler (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper discusses the role of secret versus public reserve prices when bidders' valuations depend positively on the seller's private signal. A public reserve price is announced before the auction starts, and a secret reserve price is disclosed after the highest bid has been reached. The public reserve price regime may warrant a distortion as a good seller type may have to increase the reserve price beyond payo-maximization in order to be able to credibly signal her type. We introduce and determine a rational signaling equilibrium which adds two domination-based conditions to the belief structure of a weak perfect Bayesian equilibrium. We show that a secret (public) reserve price design qualifies as an equilibrium if the distortion is large (small).
Keywords: D44; 330; auctions; interdependent values; optimal reserve prices; rational signaling